Reforming the Civil Service Compensation in Pakistan (The Pakistan Development Review, 2024)
Since the 1950s, many pay commissions and committees have been formed, but there has been no objective assessment of civil servants’ pay structure. Moreover, there has been no analysis of civil servants’ total cost, including not just the pay but all the monetary and non-monetary perks, to verify the commonly-held perception that civil servants are underpaid compared to their private sector counterparts. To fill this gap, PIDE’s report on the civil service compensation, “Cash Poor, Perk (Plots, Privileges) Rich! Civil Service Compensation in Pakistan: Incentives, Dissatisfaction, and Costs” (PIDE, 2021), looks into some key issues within the civil services. The issues that the report looks into include cash payments, non-cash rewards, inequality in the distribution of perks, waste of precious land for housing, pay and performance disconnect, a bias between cadre and non-cadre officials, and marginalised specialised groups.The analysis shows that the remuneration of a civil servant is a collection of cash payments, in-kind rewards, and intangible benefits.• The total reward of a civil servant is several times higher than the base reward (cash salary) in the contract, more so for the higher grades.• A senior civil servant’s cost to the government is several times higher than the benefits received by the official.